2020
DOI: 10.3390/cancers12051243
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs: Regulating Disease Progression and Therapy Resistance in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC), the primary liver cancer arising from hepatocytes, is a universal health problem and one of the most common malignant tumors. Surgery followed by chemotherapy as well as tyrosine kinase inhibitors (TKIs), such as sorafenib, are primary treatment procedures for HCC, but recurrence of disease because of therapy resistance results in high mortality. It is necessary to identify novel regulators of HCC for developing effective targeted therapies that can significantly interfere with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 193 publications
(254 reference statements)
0
10
0
Order By: Relevance
“… 36 Epigenetic alterations involving the chromatin remodelling machinery and ncRNAs have recently been reviewed elsewhere. [37] , [38] , [39] Herein, we review basic epigenetic mechanisms and the role of their dysregulation on hepatocarcinogenesis, focusing on DNA methylation and histone PTMs. We also highlight emerging strategies for the molecular targeting of epigenetic mechanisms with so-called “epidrugs” in HCC treatment and prevention.…”
Section: Introductionmentioning
confidence: 99%
“… 36 Epigenetic alterations involving the chromatin remodelling machinery and ncRNAs have recently been reviewed elsewhere. [37] , [38] , [39] Herein, we review basic epigenetic mechanisms and the role of their dysregulation on hepatocarcinogenesis, focusing on DNA methylation and histone PTMs. We also highlight emerging strategies for the molecular targeting of epigenetic mechanisms with so-called “epidrugs” in HCC treatment and prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The advances made in genome sequencing achieved over the past decades revealed that potentially between 97 and 98% of the human genome is transcribed into ncRNAs, which do not code for proteins but are somewhat involved in DNA replication, RNA splicing, translation, and epigenetic regulation of various biological processes, including hepatocarcinogenesis [ 99 ]. Based on their sequence length, these noncoding transcripts are divided into two groups: short ncRNAs containing less than ~200 nucleotides and long noncoding RNAs exceeding this threshold.…”
Section: The Implications Of Ncrnas In the Pathogenesis Of Nafld-rela...mentioning
confidence: 99%
“…Alterations appear to be more frequent in lysine MTs (KMTs) and lysine MDs (KDMs) than in HATs or BRD proteins [ 24 ]. The increasing knowledge about the epigenetic mechanisms involved in liver carcinogenesis (for recent reviews see [ 25 , 26 , 27 , 28 ]) ( Figure 2 ) opens perspectives for novel therapeutic approaches for HCC treatment.…”
Section: Epigenetic Mechanisms In Hccmentioning
confidence: 99%